About the role of melt movement during of the silicon single crystal growth by FZ method - Егоров, Сергей Геннадьевич (Technology audit and production reserves, 2012)
In work the conditions of occurrence of convection in the melted zone during growth of silicon single crystals by the floating zone melting method was investigate. It are fix, that streams in the melted zone (thermogravitational, centrifugal, thermocapillary and electrodynamic) influenced on distribution of impurity in the melt and, hence, defined quality of end production